Why are companies offshoring innovation? The emerging global race for talent - Lewin, Arie Y; Massini, Silvia; Peeters, Carine (Journal of International Business Studies, 2009)
This paper empirically studies determinants of decision by companies to offshore innovation activities. It uses survey data from the international Offshoring Research Network project to estimate the impact of managerial intentionality, past experience, and environmental factors on the probability of offshoring innovation projects. The results show that the emerging shortage of highly skilled science and engineering talent in the US and, more generally, the need to access qualified personnel are important explanatory factors for offshoring innovation decisions. Moreover, contrary to drivers of many other functions, labor arbitrage is less important than other forms of cost savings. The paper concludes with a discussion of the changing dynamics underlying offshoring of innovation activities, suggesting that companies are entering a global race for talent.